A Long‐Term Comparison of Hydrology and Plant Community Composition in Constructed Versus Naturally Occurring Vernal Pools. Issue 6 (26th February 2013) - Collinge, Sharon K.; Ray, Chris; Marty, Jaymee T.
Abstract Successful restoration of ephemeral wetlands worldwide is particularly challenging, given the often‐precise relationship between hydrological features and plant community dynamics. Using a long‐term experiment in vernal pool restoration, we compare hydrological and vegetative characteristics of constructed pools with those of adjacent, naturally occurring reference pools. Although constructed and reference pools were similar in maximum water depth and duration of inundation at the beginning of our experiment in 2000, constructed pools were shallower and inundated for shorter periods by 2009. Native vernal pool species were able to establish populations in many constructed pools, and seeding sped their establishment. Comparing seeded plots in constructed pools with unseeded plots in reference pools, we found no significant difference in the cover of seeded species, native species, or exotic species in most years. In recent years, however, native species have declined in both constructed and reference pools. Finally, the cover of native vernal pool species was positively and non‐linearly associated with both water depth and seeding treatment. We conclude that the establishment of appropriate hydrological conditions was necessary, but not sufficient to promote successful performance of vernal pool species in constructed pools. Constructed pools with hydrologic conditions similar to those of reference pools were more likely to support populations of native vernal pool plant species, but only seeded pools were similar to reference pools in abundance of native cover. Most importantly, hydrological conditions in experimental pools have worsened since their construction, which may hamper persistence of native species in this restoration effort.